The type of culture at a high performance schools and low performance school in the state of Kedah - Daud, Yaakob (Canadian Center of Science and Education, 2015)
This research aims to identify the type of culture at a High Performance School (HPS) and Low Performance School (LPS) in the state of Kedah. The research instrument used to measure the type of organizational culture was adapted from Organizational Culture Assessment Instrument (Cameron & Quinn, 2006) based on Competing Values Framework Quinn and Rohrbaugh (1983) Model.Two HPSs and two LPSs representing 129 teachers were chosen as research samples.Research findings showed that the current dominant culture in both HPS and LPS is Hierarchy (M=36.76, M=30.63 & SD = 8.23, SD=7.83) consecutively. Both types of schools practice Market culture and the average scores for both types of schools are the same whereby HPS (M=25.7,SD=8.56) and LPS (M=25.94, SD=8.32). However, HPS practices less Clan culture (M=21.15, SD=8.74) compared to LPS (M=24.18, SD=6.97). The Clan culture is more prominent in LPS compared to HPS. Both types of schools practice Adhocracy less which are (M=17.75, SD=6.94) in HPS and (M=19.81, SD=6.78) in LPS respectively. The findings showed that teachers in both types of schools would like to have the Clan culture practiced in their schools with the same average scores, M=34.89, SD=8.22. HPS prefers the Market culture (M=26.01, SD=6.32) compared to LPS Market culture (M=23.01, SD=.22). However they accepted Adhocracy less in HPS (M=20.02, SD=8.31) and LPS (M=21.58, SD=7.89). Nevertheless, Hierarchy culture in HPS (M=19.32, SD=6.45) and in LPS (M=21.05, SD=6.68) are widely practiced. From the comparisons made, it can be concluded that both types of schools widely practice the Hierarchy and Market cultures in schools.The recommendations for further studies were also suggested.